Factors associated with perceived stress in students appearing for medical university entrance test: A cross-sectional study - Saleem Ullah Abro, Qurratulain Saleem, Amna Begum, Jamal Ara, Nabeel Khan, Taif Hameed (Journal of Rawalpindi Medical College, 2022)
Objective: To evaluate the factors or stressors associated with perceived stress in students appearing for university entrance test-cross sectional study. Materials and Methods: It is a descriptive cross-sectional study, duration was two months from August to September 2021. The Ethical & scientific review committee of KMDC of Karachi, have given written permission. The non-probability convenience sampling technique was used. The Rao soft calculator was used for Sample size and 377 (5% margin of error and 95% confidence level) were calculated. Students were enrolled from four Entrance test/ aptitude training centers of Karachi with written informed consent. The students were having past history of antipsychiatric illness or having history of taking drugs like antidepressants or anxiolytics were excluded. The Cohen’s scale was used for evaluation of perceived stress in students with degree of perceived stress. The statistical Analysis was done by using IBM-SPSS version 23.0, Counts with percentages, Pearson Chi Square test and Binary Logistic Regression Analysis for identification of Risk Factors of Stress. P-value less than 0.05 was considered statistically significant. Results: The association of perceived stress was significantly associated with Mothers job/ working Mother (p<0.05) in our study participants. Anyone from family or friend was suffering from Stress showed significant (p<0.05) association with perceived stress (moderate / high level) in our study. Conclusion: In our study results, factors associated with perceived stress in students, showed working mothers are responsible for development of stress in students.